Code Switching Used by the Characters in “13 Bom di Jakarta” (2023) - Akmal Rizky Syahputera; Salwa AlZammy; Dhuha Hadiyansyah (UniversitasAl Azhar Indonesia, 2025)
Code-switching is a common linguistic practice in multilingual societies and often appears in modern Indonesian films as a reflection of bilingual communication. In 13 Bom di Jakarta (2023), characters frequently alternate between Indonesian and English, suggesting that language choice plays an important role in shaping identity, emotional expression, and social interaction. This study aims to identify the types and communicative functions of code-switching used by characters in the film. Using a qualitative research design with a content analysis approach, data were collected through the transcription of dialogues containing instances of code-switching. Each case was categorized based on Poplack’s code-switching typology and Appel and Muysken’s communicative function framework. The findings show that from 25 identified instances, intra-sentential switching was the most dominant type (68%), followed by inter-sentential switching (24%) and tag switching (8%). Regarding communicative functions, the referential function was used most frequently (44%), followed by expressive (24%), directive (20%), metalinguistic (8%), and poetic functions (4%). These results indicate that code-switching in the film is purposefully employed to convey technical meanings, express emotions and identity, give instructions, and create stylistic effects. The study contributes to sociolinguistic research and enriches the discussion on bilingual representation in Indonesian popular media.Keywords – Bilingualism, Code-Switching, Indonesia Films, Language Function, Sociolinguistics.